Histoplasmosis mimicking primary lung neoplasm - Kooblall, Minesh (BMJ Publishing Group, 2014)
A 70-year-old man, ex-smoker with a 3-pack-year smoking history, presented with a 5-week history of persistent cough. There were no positive findings on clinical examination. The patient's chest X-ray showed a nodular density in the right lung, initially thought to be malignant. After an extensive workup which included CT-guided lung biopsies, bronchoscopies, positron emission tomography scanning, among many other investigations, discussion at the respiratory multidisciplinary team meeting, and a right upper lobe lung resection, a diagnosis of histoplasmosis was performed.